(untitled) (American Journal of Islam and Society, 2024)
In the post-Arab Spring period, Abdullah Bin Bayyah has emerged as one of the principal exponents of the anti-revolutionary front. Dissatisfied with the Islamist solution to the socio-political crisis in the Middle East, Bin Bayyah has called for the establishment of a new jurisprudence based on fiqh al-wāqiʿ (jurisprudence of reality), which acknowledges and accepts the dictates of modern reality. He conceived his call for renewal (tajdīd) as one of the best ways to restore peace and unity in Muslim societies. This article aims to shed light on those aspects of Bin Bayyah’s reformist discourse that directly affect how he envisions the role and function of the umma in the modern context. The essay then explores the place that ummatic unification occupies in Bin Bayyah’s discourse and the kind of Islamic politics his post-Arab Spring religious discourse entails. Particular attention is also paid to the ways Bin Bayyah theorizes the significance of religious allegiances within the modern nation-state. The essay also considers Bin Bayyah’s view of the role of the Muslim umma in the global community, its relationship with other religions, and the wider human community when responding to global challenges.